Um serviço socioassistencial da cidade de São Paulo em conflito com as demandas da população em situação de rua: uma análise a partir da entrevista aplicada - Cordeiro, Diego Borges (Pontifícia Universidade Católica de São Paulo, 2018)
This article aims to analyze a social assistance service of the city of São Paulo, known as Tenda Bela Vista, whose equipment turns to the service of the homeless population. But the analysis looks exclusively at Tenda’s conflicting appointments to try to understand their quality, their demands and needs, as well as their limits and capacity. The research is based on a bibliography of the social sciences that approaches or establishes theoretical relations on the subject; an interview was also conducted with fifteen (15) homeless people, who were served by the service in 2016.